Data Classification and Access Control in Indonesia One Map Policy Geoportal - Bayu Purwanto (Journal of Applied Geospatial Information, 2022)
Indonesia has a data access policy on one map policy geoportal. Users at each level of government have different access rights to data. The President has full rights to view and downloads the data, while the governor or regent can only see certain attributes and download only its region on the same data. Data in one map policy geoportal must be able to facilitate the differences in access rights. The one map policy geoportal uses a service query system to facilitate the classification of access to process view data. In the process of downloading data geoportal using database queries. The choice of download data through the database is based on the results of the test download data from the database and service. These results indicate that downloading data through the database is faster than downloading data through a service.